Program Production Management Gen FM Network Radio - Shabrina Ayu Roshandy (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2022)
These days, the growth of media usage has encouraged the development of new media in quantity and the form itself. With these amount of media development, it leads to the inevitable competition. Radio is no exception. Today, the phenomenon of Radio Network development in Indonesia is very rife. If we see this networking practice between radio(s), then we will find a strong bond that will give many advantages for the main radio of the holdings. However, Gen FM which has their radio network in Surabaya, gives the freedom to their radio network to grow by their own. In fact, both of these radio are successfully topped the Nielsen Research. This research uses qualitative method and aim to find out how the production management program conducted by Gen FM to its radio network. The result of this study indicate that the production management program on Gen FM radio runs very well in accordance with the elements of broadcasting management including planning, organizing, actuating, and controlling. Thereby, two of these radio network can compete on top list of Nielsen.